AUS SISI PAHAT CM T5115 PADA POSES PEMESINAN LAJU RENDAH SAMPAI TINGGI PADA BAHAN JIS GRADE DF-3 - Tarigan, Janri Bastanta; Yunus, Surya Murni (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2017)
The manufacturing industry faces a paradigm in increasing productivity. Besides that that must be a concern, namely the environmental impact due to the production process, for that the metal cutting industry tries to implement environmentally friendly cutting methods. This study aims to analyze tool wear (Vb) that is useful to provide characteristic information and wear mechanism on the dry machining process , low and high speed cutting, carbidatipe chisel VNMG 332 CM T5115 Tungaloy production is used for turning the JIS GRADE DF-3 steel material, to get tool failure mode and tool wear mechanism against cutting temperature. Machining is done by machining the low and high rate cutting where the cutting speed varies (v), the cutting depth (a) and the feeding motion (f) at the maximum cutting rate condition. The lowest tool wear occurs in JIS GRADE DF-3 steel material, in the low rate machining process with the first treatment where v = 137 m/min, f = 0.50 mm, a = 1.00 mm, Aus Tool (Vb) = 0.075 mm and the highest wear wear occurred in the steel material JIS GRADE DF-3 in the high-speed machining process with the fourth treatment where v = 256 m / min, f = 0.50 mm, a = 1.00 mm, wear tool (Vb) = 0.522 mm. From the results of the characteristics of the tool failure method that occurs is worn out side. Judging from the wear of the tool to the cut temperature the wear of the tool occurs due to the influence of the depth of cut (a), cutting speed (v) and sticking furiously on the tool's eye.